Seropositivity rate of Middle East Respiratory Syndrome Coronavirus among Iraqi dromedary Arabic camels: Karim S. Ali Al-Ajeeli1; Abdulrazak SH. Hasan2 and Usama Abdul karim Ayish3 - Al-Ajeeli, Karim S. Ali (The Iraqi Journal of Veterinary Medicine, 2018)
This study was conducted to determine the Middle East Respiratory Syndrome Coronavirus infection rate among Iraqi dromedary camels and to explore its risk factor. A total of 167 blood samples were collected, ninety of them were selected randomly and included in the study from 50 males (55.6%) and 40 females (44.4%). The age range was 1-15 years. Samples were collected from Al Najaf-slaughter house. Sera were separated and tested for the presence of anti-MERS-CoV IgG using the recombivirus Camel anti-MERS-CoV spike protein S1 domain (MERS-S1) IgG ELISA kit. The results revealed that 81(90.0%) of camels included in this study were positive for anti-MERS-CoV IgG, with 95% confidence interval for the prevalence rate (82.5-94.9). Additionally, the Inter-quartile range of anti-MERS-CoV IgG titer was (5-19.7) and a mean rank of 99.8 U/ml. The highest positivity rate was among camels 10-15 years old with statistically insignificant difference (P= 0.88). Similarly, the anti-MERS-CoV IgG Ab titer was insignificantly higher in the same age group (P= 0.79). The anti- MERS-CoV IgG positivity rate was equally distributed among female and male camels (90.0%), so the difference was statistically insignificant (P=1). While the mean, median and Inter-quartile range of anti-MERSCoV-IgG titer was insignificantly higher among males compared to females (P=0.57). In conclusion, the majority of Iraqi camels are infected by MERS-CoV. Further studies are urgently needed to explore the ability of Iraqi camels to transmit the virus to human population.